Ethics in the translation of children's literature: an analysis of two Journey to the Center of the Earth translations - Silva Rando, Fernanda (2015)
The translators of children’s literature should pay attention to a very particular issue regarding the asymmetrical relationship that the adult has with his potential target public, that is, children and teenagers. Therefore, the translator of texts for this public, besides being influenced by his social, historic and cultural context, as well as any other translation, deals also with his concepts about children. So this article seeks to analyze some aspects of translation of children’s literature and the strategies used to translate and/or adapt, especially, first names, technical terms ad foreignisms. The corpus consists of two translations of the French book, by Jules Verne: Voyage au centre de la Terre (Journey to the Center of the Earth); and the theoretical foundation bases mainly on the concept of ethics in the translator process (VENUTI 2000; BERMAN, 1995 e 2013; OLIVEIRA, 2005, 2006, 2007 e 2008). The analyses were carried out in a comparative way, and not evaluative, of some excerpts, from several chapters, that illustrate different ethic procedures.